PENGARUH TINGKAT SUKU BUNGA, INFLASI DAN PERTUBUHAN GROSS DOMESTIC PRODUCT TERHADAP JUMLAH UANG BEREDAR DI TIMOR-LESTE - Augusto Maria, José; Sedana, I B. Panji; Sri Artini, Luh Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The increasing of the money supply is a measure one of the economic growth of a country. Money has a strategic role in the economy, especially since its main function as a medium for transactions, so that at first is often translated into a common unit that can be accepted as means of payment (Putong Iskandar, 2007). The location of the research conducted at the Central Bank of East Timor has referred on the annual reports of the IMF and World Bank with the period 2004 – 2013. The collect method analysis data is using the quantitative data. The results obtained in the studies analyzed variables using the multiple regression analysis program SPSS. The results showed that use of the three variables, namely interest rates, inflations and Gross Domestic Products is only the interest rate and inflation is significant negative effect on the money supply, this means that if the central bank reduces the amount of money circulating in East Timor can be done with rising interest rates and government fiscal policy.